Saringan Cangkang Telur Bebek Efektif Memperbaiki Kualitas pH Dan Kadar Besi Air Sumur Bor - Rahmatullah Jati Pradopo; Sulaiman Hamzani; Syarifudin A. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Water well drill that is in the Pondok Pesantren Hidayatullah Banjarbaru seen physically yellowish and smelly. Preliminary test result obtained pH 4.9 and Fe 2.5 mg/L. Based on the quality of clean water standards have not fulfilled the requirements of 1.0 mg/L and pH 6.5-8.5. It needs to be done research test of duck egg filter making in improving the quality of pH and Fe water well drill. The goal of this research is to know the effectiveness of duck egg filter in improving the quality of pH and Fe water wells drill. Types of research are experiments with pretest-posttest with control group. The population in the research is the whole water well drill in the Pondok Pesantren Hidayatullah Banjarbaru. A research sample is a water well drill that is partially taken for trial. Analysis of the influence thickness of the sieve using Anova asymp Test < œ (0.000 < 0.05) means there is a difference between the filter thickness of duck egg, 0 cm, 20 cm, 40 cm, 60 cm. Then done test Posh Hoc Tests can be concluded that there is a meaningful difference between the thickness of the filter of ducks egg shells 0 cm, 20 cm, 40 cm, 60 Based on the research results of the sieve 40 cm with a weight of 291 gram is an effective sieve in lowering the water level of the well drill.